Dilatancy Toughening of Shear Cracks and Implications for Slow Rupture Propagation. Issue 11 (19th November 2021) - Brantut, Nicolas
Abstract: Dilatancy associated with fault slip produces a transient pore pressure drop which increases frictional strength. This effect is analyzed in a steadily propagating rupture model that includes frictional weakening, slip‐dependent fault dilation and fluid flow. Dilatancy is shown to increase the stress intensity factor required to propagate the rupture tip. With increasing rupture speed, an undrained (strengthened) region develops near the tip and extends beyond the frictionally weakened zone. Away from the undrained region, pore fluid diffusion gradually recharges the fault and strength returns to the drained, weakened value. For sufficiently large rupture dimensions, the dilation‐induced strength increase near the tip is equivalent to an increase in toughness that is proportional to the square root of the rupture speed. In general, dilation has the effect of increasing the stress required for rupture growth by decreasing the stress drop along the crack. Thermal pressurization has the potential to compensate for the dilatant strengthening effect, at the expense of an increased heating rate, which might lead to premature frictional melting. Using reasonable laboratory parameters, the dilatancy‐toughening effect leads to rupture dynamics that is quantitatively consistent with the dynamics of observed slow slip events in subduction zones. Plain Language Summary: During fault slip, microscopic voids often open in the material forming the core of the fault, leading to a succion effect that can decompress the fluid present in the pores of the rock. This decompression strengthens the rock. At large scale, such a strengthening leads to an increase in the energy or load required to propagate the fault, leading to slower rupture speeds than otherwise anticipated. Key Points: Dilatancy strengthening leads to an increase in toughness of expanding shear cracks, which grows with increasing rupture speed Crack propagation can be limited by the rate of fluid recharge far behind the crack tip Dilatancy effect with reasonable parameter values is consistent with the dynamics of slow slip in subduction zones